Improvement of Teachers Is the Key to the Progress in Learning Foreign Languages - Sadikova Mukaddam (International Journal on Integrated Education, 2022)
This article analyzes a teacher's management skills in foreign language classes. It describes the situations that may arise in the practical application of modern educational technologies.